Constructing the resilient subject in Israeli classrooms: professional interventions, culture and politics in a protracted conflict - Plotkin Amrami, Galia; Brunner, José (Pedagogy, culture & society, 2017)
While the concept of resilience has attracted a great deal of academic interest, less attention has been paid to the particular traits of the resilient subject. This article extracts the prototype of the resilient student as performed through professional interventions that build resilience in Israeli schools in the context of the Israeli-Palestinian conflict. Drawing on sociological scholarship that interweaves the domains of therapeutic discourse and cultural context, we describe the resilient subject not only as a psychological but also as cultural prototype and a national subject. We demonstrate that professional practices foster the ability to process feelings, think rationally and control instinctive emotional and bodily reactions to avoid violent behaviour. This ethics of non-violence draws on the western cultural ideal of a normative personality rather than on a particular political context. However the impact of professional interventions on the design of students' civil beliefs regarding the conflict might warrant consideration.